Psychometric Properties of the Iranian Religious Coping Scale in the Indonesian Context: Validation and Adaptation - Mamang Efendy; Nindia Pratitis; Amhersita Pasca Rina (Tazkiya Journal of Psychology, 2026)
In the last decade, Indonesia has experienced a remarkable surge in the development of religiosity assessment tools; nevertheless, validated scales specifically designed to measure religious coping continue to be conspicuously scarce. This study examined the construct validity of the Iranian Religious Coping Scale (IRCS) adapted for Indonesian Muslim university students. Religious coping is a belief-based cognitive–behavioral strategy that has been shown to support stress management and psychological well-being. Following a rigorous translation and cultural adaptation process, the IRCS was translated into Bahasa Indonesia, back-translated, reviewed by experts, and tested for readability with ten students. The final instrument consisted of 22 items across five dimensions: Religious Practice, Negative Feelings toward God, Benevolent Reappraisal, Passive Religious Coping, and Active Religious Coping. Data were collected from 804 university students (Mean age = 21.23 ± 3.73 years; 65.7% female) through an online survey. Construct validity was tested using Confirmatory Factor Analysis (CFA) in JASP. All items showed significant factor loadings on their respective dimensions (λ = .425–.940, p < .001). The model demonstrated good fit (CFI = .957; TLI = .950; RMSEA = .049; SRMR = .035), supporting the five-factor structure. The Negative Feelings toward God dimension showed the strongest loadings, while Benevolent Reappraisal demonstrated moderate but acceptable values. Overall, the Indonesian version of the IRCS exhibited satisfactory construct validity and cultural appropriateness. The scale is suitable for use in psychological research and practice in Indonesia to assess religious coping strategies. Future studies should involve more diverse populations to enhance the generalizability of the findings.